Factors associated with non-invasive ventilation failure and mortality in oncologic patients outside the intensive care unit (Research, Society and Development, 2021)
Introduction: New treatments have been introduced with the objective to increase the survival rate of oncologic patients. As a result of these approaches, there was an increase in the number of cases of toxicity and complications, which can lead to acute respiratory failure (ARF). One of the most frequent ways to treat ARF is non-invasive ventilation (NIV). Despite the proven benefits in several clinical conditions, NIV results in cancer patients are controversial. Objective: To evaluate risk factors associated with NIV failure and hospital mortality in oncologic patients. Methods: Retrospective cohort study including patients with solid tumors and hematological neoplasms admitted for hospitalization at National Cancer Institute between January 1, 2017 and December 31, 2019, who underwent NIV. The association between the variables of exposure and the outcome was performed by gross and adjusted logistic regression. The Kaplan-Meier method was used to analyze the length of hospital stay. Results: Sixty-three patients who underwent NIV in hospitalization were evaluated, and 26 failed NIV. The patients had a mean age of 58.5 years (±15.6), most were male (57.1%), under 60 years old (58.7%) and had comorbidities (55.5%). The patients with pulmonary infection (OR 6.53; 95% CI 1.21-35.12; p=0.02) had a higher risk of failure in NIV. In relation to hospital mortality, patients older than 60 years (OR 6.90; 95% CI, 2.12-22.45; p=0.001) had a higher risk. Conclusion: Patients who presented pulmonary infection were more likely to fail in NIV. Higher hospital mortality was observed among elderly patients.